Resource allocation algorithm for secure communication in UAV-assisted D2D communication network - Xiaowan ZENG; Haijun WANG; Lei HUANG; Dongtang MA (Tongxin xuebao)
To solve the problems of energy limitation, spectrum shortage, and serious co-frequency interference in the unmanned aerial vehicle (UAV)-assisted D2D (device-to-device) communication network under passive eavesdropping, the concept of the network secrecy energy efficiency was introduced by taking into account the secrecy rate and transmit power constraints of each user.Based on the physical layer secure transmission theory, the joint optimization problem of spectrum multiplexing and power control strategies was investigated to maximize the network secrecy energy efficiency.The problem was a nonlinear nonconvex problem, a resource allocation algorithm combining Dinkelbach’s algorithm and the convex approximation algorithm was proposed to transform the nonconvex optimization problem into a geometric planning problem through the convex approximation algorithm and ensure that the original problem converges to the global optimal solution by Dinkelbach’s algorithm.Simulation results show that the proposed algorithm can effectively mitigate the co-channel interference, improve the network secrecy energy efficiency, and balance the relationship between the secure communication performance and power consumption of the network.